FIRST PERSONAL DEIXIS IN 10-17 AGED CHILDREN’ UTTERANCES OF MINAGKABAU LANGUAGE IN SARIAK, BANUHAMPU SUNGAI PUAR SUBDISTRICT, WEST SUMATERA - Yusra Dewi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract Deixis utilization uniqueness in 10-17 aged children’ utterances of Minangkabau language resulted in the conduction of this research. Unique thing of Minangkabau language phenomenon was, in addition, the orientation for the formulation of the research problems. There were two kinds of research questions, namely: 1) What are first personal deixis forms realized in 10-17 aged children of Minangkabau language in Sariak village, Banuhampu Sungaipuar sudistrict, West Sumatera?; and 2) How is first personal deixis utterances used? The objective of this study is to describe the forms and the use of first personal deixis utterances. The research was designed by using qualitative descriptive research approach. The data was verified by illustrating evidences according to Metode Simak ‘refer to method’ and Metode Cakap ‘Advanced Method’ which are divided into some techniques. Metode Simak consists of basic technique and advanced technique. Advanced involving free referred to technique, recording technique, and note-taking technique. Meanwhile, advanced method is divided into basic technique including note-taking technique and eliciting technique. The data of the research were words and phrases in utterance form.the data was obtained from Minangkabau language used by 10-17 aged children in Sariak villaged, Banuhampu Sungaipuar subdistrict, West Sumatera. Trustworthiness of data was examined by data triangulation technique. The finding shows that there six types of first personal deixis realized in 10-17 aged children’ utterances of Minangkabau. The forms of 10-17 aged children’ utterances of Minangkabau language are sayo, ambo, aden, nama diri, aku, kami, awak, denai, kito ‘I’. Utilization of first personal deixis in the utterances of 10-17 aged children is adapted to when, where and who the utterances take place. Keywords: Personal deixis, children’ utterance, Minangkabau language